Children in Need of Medical Innovation - Horst Entorf; Jörg Fegert; Michael Kölch (Technische Universität Darmstadt, Department of Law and Economics, 2004)
Children are therapeutic orphans and an underprivileged group in innovations derived from drug therapy. As the innovation process of pharmaceuticals is a long, risky and very costly business, economists typically emphasise lack of profit incentives and small market size as the most important obstacles to child-related innovative activity. Moreover, as new drugs need to be tested in medical trials, there are ethical concerns leading to a climate of reluctance towards medical trials on persons who are not able to give their "informed consent". Particularly in Germany, due to various reasons, a rather restrictive legislation is to be assumed, characterized by the idea of putting the protection of the individual human being before a more utilitarian view. Thus, economic incentives, legal restrictions and ethical concerns seem to be responsible for the lack of innovative activity targeted at drugs for children, though social cost-benefit considerations (i.e. welfare analysis) would most probably predict a high gain from the introduction of critical innovations. Grounded on a highly interdisciplinary view based on medical, pharmaceutical, psychopharmaceutical, psychotherapeutic and economic research as well as on ethical restrictions, this survey aims at analysing channels of influence that might be helpful both in the analysis of the innovation process of drugs for children, and in improving the uncertain situation of pediatric therapy.
Keywords: 330; Pharmazeutische Forschung; Kinder; Medizin; Innovation; Marktversagen; Kosten-Nutzen-Analyse